The regulation of carotenoid formation in tomato fruit. (7th February 2017) - Enfissi, Eugenia M.A.; Nogueira, Marilise; Bramley, Peter M.; Fraser, Paul D.
Summary: Carotenoid biosynthesis in plants includes a complex series of desaturation/isomerisation reactions, catalyzed by four independent enzymes. In bacteria and fungi one desaturase/isomerase enzyme completes the same series of reactions. In the present study, a bacterial desaturase ( crtI ) from Pantoea ananatis has been overexpressed in the tangerine mutant of tomato ( Solanum lycopersicon ) which accumulates cis ‐carotene isomers in the fruit due to a defective isomerase (CRTISO) and the old gold crimson ( og c ) tomato mutant, which is defective in the fruit‐enhanced lycopene β‐cyclase ( CYCB ). Comprehensive molecular and biochemical characterization of the resulting lines expressing crtI has revealed negative feedback mechanisms, acting predominantly at the level of phytoene synthase‐1 ( PSY1 ), and feed‐forward mechanisms inducing cyclisation. In both cases, altered transcription appears to be the progenitor, with subsequent post‐transcriptional modulation highlighting the complexity of the processes involved in modulating carotenoid homeostasis in plant tissues. Significance Statement: Carotenoid biosynthesis in plants includes a series of desaturation/isomerisation reactions, catalysed by four independent enzymes; in bacteria these reactions are catalysed by one enzyme, the crt I like phytoene desaturase. Expressing crt I in plants confers resistance to bleaching herbicides and enhances provitamin A content, e.g. in Golden Rice. Here we introduced crt I into tomato mutants defective in two different steps in the carotenoid biosynthetic pathway to determine how the endogenous carotenoid pathway reacts to alterations in desaturation. Collectively our data provide insights into the mechanisms operating within the pathway and how multi‐level metabolite changes can occur.